2023
DOI: 10.1021/acs.jpcc.3c02137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Irradiation on Hot Electron-Mediated Photoreduction of Silver Ions on Single Gold Nanorods without a Reducing Agent

Abstract: This study investigated the hot electron-mediated photoreduction of silver (Ag) ions on gold nanorods (AuNRs) exposed to a silver nitrate (AgNO3) solution under white light irradiation without a reducing agent and the effect of white light irradiation on the structural and spectral changes in single AuNRs. The hot electron-mediated Ag deposition was confirmed to occur upon white light irradiation, producing AuNRs@Ag (core@shell) structures. No noticeable changes in the size of AuNRs@Ag in the transverse and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Based on the above review of fundamentals and recent advances, it becomes apparent that depending on the precise mechanistic role of LSPR excitation in a metal nanoparticle synthesis there are significant differences is the extent of structural control that is currently achievable using visible light as a driving force. For reactions where the mechanism involves direct reduction of metal ions by LSPR-induced hot electronssuch as in the deposition of Pd, Pt, or Ag onto preformed Au nanoparticlesstructural control is primarily limited to the formation of core–shell nanostructures. ,,, An exception to this is the plasmon-mediated synthesis of Au nanoprisms and nanostars, where hot electron-driven growth was successful in controlling particle shape with assistance from surface adsorbates, such as PVP and iodide. , This suggests that the participation of surface-adsorbed species may be critical for successful shape control in hot electron-driven nanoparticle synthesis moving forward. For example, the adsorption of molecules with hole-scavenging or electron-relay capabilities that are pH tunable and/or bind in a facet-specific manner could provide a mechanism of finely tuning metal ion reduction rates and thus nanoparticle shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above review of fundamentals and recent advances, it becomes apparent that depending on the precise mechanistic role of LSPR excitation in a metal nanoparticle synthesis there are significant differences is the extent of structural control that is currently achievable using visible light as a driving force. For reactions where the mechanism involves direct reduction of metal ions by LSPR-induced hot electronssuch as in the deposition of Pd, Pt, or Ag onto preformed Au nanoparticlesstructural control is primarily limited to the formation of core–shell nanostructures. ,,, An exception to this is the plasmon-mediated synthesis of Au nanoprisms and nanostars, where hot electron-driven growth was successful in controlling particle shape with assistance from surface adsorbates, such as PVP and iodide. , This suggests that the participation of surface-adsorbed species may be critical for successful shape control in hot electron-driven nanoparticle synthesis moving forward. For example, the adsorption of molecules with hole-scavenging or electron-relay capabilities that are pH tunable and/or bind in a facet-specific manner could provide a mechanism of finely tuning metal ion reduction rates and thus nanoparticle shape.…”
Section: Discussionmentioning
confidence: 99%
“…In two of these cases, low energy excitation in the near IR was used to excite the longitudinal LSPR resonance of the Au nanorods (810 nm), thus eliminating any contributions from interband excitation of the Au nanorods and providing evidence of a mechanism in which Pt 4+ is reduced by hot electrons generated from the excitation of intraband transitions . Hot electron-driven enhancement of the reduction rate of Ag + ions (from AgNO 3 ) onto Au nanorods in the absence of any hole scavenger or reducing agent has also been reported, in contrast to previous work where Ag + reduction was driven by thermalized electrons following the oxidation of a reducing agent by hot holes. ,, In most of these examples, the resulting product was a Au nanorod or nanosphere core with a thin, epitaxial shell of the second metal. However, in one case Pt formed clusters at the tips of the Au nanorod, and detailed study of Pt deposition onto Au nanorods suggested that Pt deposition may first begin at the tips due to enhanced localization of hot electrons at these sites, while the hole scavengermethanolis localized on the edges of the rods. , Additional study is required to validate or disprove this mechanism.…”
Section: Bimetallic Hybrid Materialsmentioning
confidence: 96%
“…The authors attribute photopolymerization activity to plasmon-induced generation of monomer radicals and deem local photothermal heating to play a negligible role. Lee and Ha employed single-nanoparticle studies to elucidate hot-electron-mediated reduction of Ag onto Au nanorods without a reducing agent.…”
Section: Mechanistic Studies Of Hot-electron Catalysismentioning
confidence: 99%